Penerapan Metode Tahsin dalam Meningkatkan Kemampuan Membaca Al Qur'an Santri TPQ Al Barokah Seling - Saniyatul Khoiriyah; Siti Fatimah; Faisal Faisal (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the increase in reading ability of the Qur'an of TPQ Al Barokah Al-Barokah students in Karanggulung using the tahsin method. This research is a classroom action research conducted in two cycles, each cycle consisting of two meetings. Each cycle is carried out planning implementation and observation. The subjects of this study were all 15 children who recited the Koran at TPQ. Data collection techniques using observation, interviews, documentation, and tests. The results of the analysis show that as many as 53.33% of the students get a complete score in the Al-Qur'an reading ability assessment. Whereas in cycle II as many as 93.33% of students obtained a complete score in assessing the ability to read the Qur'an after using the tahsin method. So it can be concluded that there was an increase in the ability to read the Qur'an after using the tahsin method in TPQ Al Barokah children.